Climate Smart Village Project: Farmer testimonial on minimum tillage - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) has introduced the model of "Climate Smart Villages (CSVs)" in India, and is slowly scaling up and expanding to other countries in the South Asia region. The idea is to raise awareness among farming communities in South Asia about various technological, institutional and policy-oriented options that have the potential to increase their climatic resilience, adapt to climate change, increase agricultural productivity and income, while reducing emissions of greenhouse gases. In this video, you will learn more about the benefits from limiting tillage being promoted within the project and hear the testimonials from farmers who have tried the practice. Read more: http://ow.ly/kXVFR